Knowledge and perception with intention in the selection of postpartum intrauterine contraceptive device in third trimester pregnant women - Devi Nur Rochmawati; Niken Meilani; Arif Nugroho Triutomo (Jurnal Kesehatan Ibu dan Anak, 2022)
Family Planning Program was one strategy to reduce the risk of maternal death. The first year postpartum was the most important time for contraceptive use. The percentage of intrauterine contraceptive device(IUCD) usage was still low compared to other contraceptive methods. The aim of this study was to know the relationship of knowledge and perception with intention in the selection of postpartum intrauterine contraceptive device(PPICD) in third trimester pregnant women. This study was an analytic observational study with a cross-sectional design. The study was conducted in June 2022. Data for pregnant women in the third trimester of July 2021 - August 2021 at the Dadirejo Public Health Center are 72 people. This research uses total sampling. The research instrument is a questionnaire. Data analysis in this study was univariate, bivariate (Chi-square and likelihood) and multivariate (logistical regression) analysis. The proportion of postpartum contraceptive use was 52%. Knowledge level (p=0.000), perception (p=0.000) was related to the intention to use the PPIUCD. The variable that most influenced the intention to use the PPIUCD was the level of knowledge OR 15.315 (95% CI 3.337-69.4531; p=0.000). Knowledge level is the most dominant factor.